Intervention package on stress management: Improving comprehensive well-being among nurses - Manda Jaywant Phuke; Tukaram Zagade; Vaishali Rajsinh Mohite; Jyoti Salunkhe; Swati Ingale; Samir Kasam Choudhari (Journal of Integrative Nursing)
Objective: The main objective of this study is to investigate the effectiveness of the stress management intervention package in improving stress-related burnout. Materials and Methods: An experimental study was done on 300 nurses selected by a nonprobability convenience sampling technique and a quasi-experimental one-group pre- and posttest research design was utilized. Modified expanded nurses stress scale and self-structured three-point Likert scale on the challenges that nurses may face following stressful life events utilized to collect information. The nurses signed up for six interactive sessions on various stress-coping methods by utilizing a variety of teaching strategies such as lecture cum discussion, video slides, group work, and direct interaction with the experts to explore stress-related issues. Results: Continuous stress affects both the body and the mind, causing psychosomatic symptoms. Data found that 2% to 10% of nurses frequently suffered with physical symptoms such as exhaustion, backache, acidity, headache, shoulder stiffness, and insomnia. Following the intervention, the number of nurses who had these symptoms frequently and sometimes decreased. Previously, 10% of nurses experienced emotional symptoms frequently; however, after intervention, this figure was reduced to < 2%. The greatest proportion of nurses (18%) reported frequently worrying, while 1.3% expressed frequent worrying after intervention. Maximum (5%) of nurses had a tendency to eat too little or too much; this has been reduced to 0.3% after the intervention. The intervention package on stress management significantly improved nurses’ comprehensive well-being (P < 0.0001). Conclusion: An intervention package for stress management was helpful in lowering physical, emotional, psychological, and behavioral stress-related symptoms among nurses.